Knowledge societies --in a nutshell : information technology for sustainable development - Credé, Andreas (The Centre, 1998)
In summarizing the full-length report of the Working Group (entitled Knowledge Societies), this book focuses particularly on the dangers that will accompany a failure to develop information and communication technology (ICT) strategies tailored to the specific and changing needs of countries in the developing regions of the world. It will appeal to decision-makers and ICT producers and users, as well as to development professionals, academics, and citizens interested in development issues and the new and emerging information and communication technologies.